2021
DOI: 10.1093/geront/gnab068
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence in Residential Care Facilities in New South Wales, Australia: A Text Mining Study

Abstract: Background and Objectives The police are often the first to attend domestic violence events in New South Wales (NSW), Australia, recording related details as structured information (e.g., date of the event, type of incident, premises type) and as text narratives which contain important information (e.g., mental health status, abuse types) for victims and perpetrators. This study examined the characteristics of victims and persons of interest (POIs) suspected and/or charged with perpetrating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Improved training and awareness from attending police officers can assist in the recording of key details of those involved in a domestic violence event beyond routine demographic and spatio-temporal characteristics and potentially capture information for at-risk sub-populations. Examples of this include reports of mental illness in perpetrators and victims, observed injuries not requiring hospitalization, threats, trends in specific abuse types such as non-fatal strangulation and frequency of abuse within a particular setting such as nursing homes (16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved training and awareness from attending police officers can assist in the recording of key details of those involved in a domestic violence event beyond routine demographic and spatio-temporal characteristics and potentially capture information for at-risk sub-populations. Examples of this include reports of mental illness in perpetrators and victims, observed injuries not requiring hospitalization, threats, trends in specific abuse types such as non-fatal strangulation and frequency of abuse within a particular setting such as nursing homes (16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated the successful application of text mining to a large corpus of police domestic violence event narratives to identify mentions of mental illness, abuse type(s), and victim injuries ( 16 , 17 ). We also demonstrated that the extracted information can be used to provide insights into domestic violence and mental illness ( 18 ) and in the context specific diagnoses (i.e., autism) ( 19 ), the setting (i.e., nursing homes) ( 20 ), and abuse type (i.e., non-fatal strangulation) ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a number of papers (n = 16) were found to report on the same two broad studies, using similar datasets and models. These were the Karystianis et al papers on the New South Wales Police Force data using a rule-based approach, n = 6 (Adily et al, 2021;Hwang et al, 2020;Karystianis et al, 2019Wilson et al, 2021;Withall et al, 2022), and the Poelmans et al papers on the Amsterdam-Amstelland Police Force Data using an FCA and ESOM based approach, n = 10 (Elzinga, Poelmans, Viaene, & Dedene, 2009;J. Poelmans, Elzinga, & Dedene, 2013;J.…”
Section: Included Studiesmentioning
confidence: 99%
“…These text records enable identification of the characteristics of domestic violence perpetrators (hereafter referred to as Persons of Interest (POIs) i.e., individuals involved in an event that have been accused or charged for perpetrating DV related crimes) that can inform further research, clinical screening, and interventions. Police records enable characteristics of DV events to be described ( 19 ) based on the setting (e.g., nursing homes) ( 21 ), specific mental health conditions (e.g., autism) ( 22 ) and abuse types (e.g., non-fatal strangulation, coercive control) ( 23 , 24 ), and population sub-groups ( 25 ).…”
Section: Introductionmentioning
confidence: 99%